Bullous pemphigoid—What do we know about the most recent therapies? - Zeng, Faith A. P.; Murrell, Dedee F. (Frontiers in Medicine, 2022)
Introduction Bullous pemphigoid (BP) is the most common subtype of autoimmune blistering diseases that primarily affects the elderly and is classically defined by the presence of IgG and/or complement C3 against the BP180 and BP230 hemidesmosome proteins. However, most recent studies have introduced the role of specific eosinophil receptors and chemokine mediators in the pathogenesis of BP which are helpful in identifying new targets for future treatments. Areas covered This review will focus on the involvement of eosinophils in BP, including the processes that lead to their recruitment, activation, and regulation. Subsequently, covering new therapeutic options in relation to the role of eosinophils. Eotaxin enhances the recruitment of eosinophils in BP, with CCR3 chemoreceptor that is expressed on eosinophils being identified as a key binding site for eotaxin-1. The pathogenic role of IgE and IL-4 in BP is corroborated by successful treatments with Omalizumab and Dupilumab, respectively. IL-5, IL-17 and IL-23 inhibitors may be effective given their roles in promoting eosinophilia. Expert opinion Further research into inhibitors of eotaxin, IL-4, IL-5, IL-17, IL-23, CCR3, and specific complement factors are warranted as preliminary studies have largely identified success in treating BP with these agents. Learning from novel treatments for other IgG-mediated autoimmune diseases may be beneficial.